An impact of hydrogenation phase transformation mechanism on the cyclic stabilizing behavior of Zr0.8Ti0.2Co alloy for hydrogen isotope handling. (December 2020) - Yao, Z.; Liang, Z.; Xiao, X.; Huang, X.; Liu, J.; Wang, X.; Zheng, J.; Kou, H.; Luo, W.; Chen, C.; Chen, L.
Abstract: Zr0.8 Ti0.2 Co alloy shows tremendous potential for handling hydrogen isotopes in fusion reactors. However, its severe cyclic fading remains a big challenge for achieving engineering application. Herein, we report a comprehensive study on hydrogenation phase transformation and structural evolution in cyclic stabilizing process of Zr0.8 Ti0.2 Co alloy. It is clarified that the stable capacity is provided by a metastable phase (Zr0.8 Ti0.2 CoH1.4 ) because the cyclic reaction transforms from Zr0.8 Ti0.2 Co↔Zr0.8 Ti0.2 CoH3 (heterogeneous structural phase transformation) into Zr0.8 Ti0.2 Co↔Zr0.8 Ti0.2 CoH1.4 (homogeneous structural phase transformation). In addition, structural analysis reveals the cyclic hydrogenation phase transformation mechanism. The in situ ZrCo2 and ZrH2 phases compose a porous cage structure with remarkable mechanical property on the surface, which tightly restricts hydriding volume expansion of ZrCo phase. Thus, generation of ZrCoH3 phase with higher volume expansibility (21%) is replaced by Zr0.8 Ti0.2 CoH1.4 phase (ΔV = 8%). The sparkling concept of forming metastable phase within homogeneous structural phase transformation reaction will serve as a pioneer on cyclic optimization in energy storage materials. Graphical abstract: Image 1 Highlights: A metastable phase of Zr0.8 Ti0.2 CoH1.4 is found during hydriding process in Zr0.8 Ti0.2 Co alloy. Homogeneous structural phase transformation is applied to reveal cyclic stabilizing behavior for the first time. A porous cage structure is built to demonstrate reaction transformation mechanism from B2.→B2'→B33″ to B2→B2'. Targeted modification strategy is provided for enhancing cyclic stability of hydrogen storage materials.